A carbon budget for the Amundsen Sea Polynya, Antarctica: Estimating net community production and export in a highly productive polar ecosystem - Yager, PL; Sherrell, RM; Sipler, Rachel E.; al, et (Elementa: Science of the Anthropocene, 2016)
Polynyas, or recurring areas of seasonally open water surrounded by sea ice, are foci for energy and material transfer between the atmosphere and the polar ocean. They are also climate sensitive, with both sea ice extent and glacial melt influencing their productivity. The Amundsen Sea Polynya (ASP) is the greenest polynya in the Southern Ocean, with summertime chlorophyll a concentrations exceeding 20 μg L−1. During the Amundsen Sea Polynya International Research Expedition (ASPIRE) in austral summer 2010–11, we aimed to determine the fate of this high algal productivity. We collected water column profiles for total dissolved inorganic carbon (DIC) and nutrients, particulate and dissolved organic matter, chlorophyll a, mesozooplankton, and microbial biomass to make a carbon budget for this ecosystem. We also measured primary and secondary production, community respiration rates, vertical particle flux and fecal pellet production and grazing. With observations arranged along a gradient of increasing integrated dissolved inorganic nitrogen drawdown (ΔDIN; 0.027–0.74 mol N m−2), changes in DIC in the upper water column (ranging from 0.2 to 4.7 mol C m−2) and gas exchange (0–1.7 mol C m−2) were combined to estimate early season net community production (sNCP; 0.2–5.9 mol C m−2) and then compared to organic matter inventories to estimate export. From a phytoplankton bloom dominated by Phaeocystis antarctica, a high fraction (up to ∼60%) of sNCP was exported to sub-euphotic depths. Microbial respiration remineralized much of this export in the mid waters. Comparisons to short-term (2–3 days) drifting traps and a year-long moored sediment trap capturing the downward flux confirmed that a relatively high fraction (3–6%) of the export from ∼100 m made it through the mid waters to depth. We discuss the climate-sensitive nature of these carbon fluxes, in light of the changing sea ice cover and melting ice sheets in the region.